The Rigid Finite Element Method Applied to a Riser Handling Analysis - Szczotka, Marek (Journal of Applied Nonlinear Dynamics, 2026)
Riser handling is a special operation performed by a dedicated, specialized lifting equipment operated from a production platform or vessel. A mathematical model of the system is developed, which allow us to simulate the loads acting on the lifting equipment as well as riser elements. The rigid finite element method (RFEM) is applied to discretize the system, consisting of long and flexible components like riser and various rope systems. Large deformations are common conditions in such systems and operations, which have to be accounted in the analysis. For the problem described in the paper, an FPSO (Floating Production, Storage and Offloading Unit) vessel consists of a dedicated riser pull-in winch. An another pipeline installation vessel (PLV) is used for the construction work related to riser handling. The load transfer between FPSO pull-in winch an PLV lifting winch is critical for the project specification and the design input. On the basis of calculated loads, the design of the riser pull-in winch can be concluded. A dedicated software developed enables for an user-friendly definition and execution of the riser handling analysis. Based on developed models and results obtained, the design conditions can be formulated. With the aid of developed mathematical model and the computer program, an example simulation of the riser installation is performed.